If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+(-4)=(-18)
We move all terms to the left:
x+(-4)-((-18))=0
We add all the numbers together, and all the variables
x+14=0
We move all terms containing x to the left, all other terms to the right
x=-14
| -5w-5+6w=2+2w | | 6x-4+2(5x-2)=16x | | 35√y+2=9 | | 470÷x= | | 6m+5=4m-2 | | 2h+10=-9-h+7 | | -8(8+5m)=8(7-8m) | | 3n+10=3(12) | | 1-3m=-14-6m | | 8+9t=-8+3t+8t | | -4(x+2)=-(2x-4) | | -26+3r=(-86) | | 30(56)=48x | | 7v-8=7+4v | | 8(-1-3p)=-7(3p+8) | | -16=8v+5-5 | | 2+6x=6x+2 | | -3m-3+2m=-3m+7 | | -3=5a-7-6 | | g-93/2=3 | | 8(7b+7)=-8(4+4b) | | 35x=2.5 | | 3(×+2)=x+11 | | 5.2u-3.88-2.9u=7.16+3.9u | | 2p+5p=-21 | | −52(6x+24)=x−12x= | | f(2)=29 | | (6m-12)^2=4(9)(m^2) | | -4(1-x)=-4(1-8x) | | 6d+8=98 | | p/2+8=15 | | m+13=(-39) |